External environment and internal state in relation to life-history behavioural profiles of adolescents in nine countries - Chang, Lei (Archīum Ateneo, 2019)
The external environment has traditionally been considered as the primary driver of animal life history (LH). Recent research suggests that animals' internal state is also involved, especially in forming LH behavioural phenotypes. The present study investigated how these two factors interact in formulating LH in humans. Based on a longitudinal sample of 1223 adolescents in nine countries, the results show that harsh and unpredictable environments and adverse internal states in childhood are each uniquely associated with fast LH behavioural profiles consisting of aggression, impulsivity, and risk-taking in adolescence. The external environment and internal state each strengthened the LH association of the other, but overall the external environment was more predictive of LH than was the internal state. These findings suggest that individuals rely on a multitude and consistency of sensory information in more decisively calibrating LH and behavioural strategies.